2019
DOI: 10.1257/mac.20180141
|View full text |Cite
|
Sign up to set email alerts
|

Forward Guidance and Heterogeneous Beliefs

Abstract: Central banks’ announcements that rates are expected to remain low could signal either a weak macroeconomic outlook, which would slow expenditures, or a more accommodative stance, which may stimulate economic activity. We use the Survey of Professional Forecasters to show that, when the Fed gave guidance between 2011:III and 2012:IV, these two interpretations coexisted despite a consensus on low expected rates. We rationalize these facts in a New-Keynesian model where heterogeneous beliefs introduce a trade-of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
71
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(75 citation statements)
references
References 51 publications
4
71
0
Order By: Relevance
“…We emphasize that central bank communication can affect macroeconomic expectations over long horizons, which is consistent with the work of Gürkaynak et al (2005b), Nakamura and Steinsson (2018), and Eusepi, Giannoni and Preston (2018). Consistent with the analysis of forward guidance policy provided in Andrade et al (2015), our evidence underlines that announcements of future low rates at the ZLB should be predominantly understood as Odysssean shocks if they are to be expansionary, and that they could be counterproductive if predominantly understood as Delphic shocks. We find evidence that the ECB announcements became predominantly understood as Odyssean when explicit forward guidance policy was implemented relative to the period without forward guidance policies.…”
Section: Related Literaturesupporting
confidence: 83%
See 1 more Smart Citation
“…We emphasize that central bank communication can affect macroeconomic expectations over long horizons, which is consistent with the work of Gürkaynak et al (2005b), Nakamura and Steinsson (2018), and Eusepi, Giannoni and Preston (2018). Consistent with the analysis of forward guidance policy provided in Andrade et al (2015), our evidence underlines that announcements of future low rates at the ZLB should be predominantly understood as Odysssean shocks if they are to be expansionary, and that they could be counterproductive if predominantly understood as Delphic shocks. We find evidence that the ECB announcements became predominantly understood as Odyssean when explicit forward guidance policy was implemented relative to the period without forward guidance policies.…”
Section: Related Literaturesupporting
confidence: 83%
“…Earlier studies find evidence that central bank communication about current and future rates conveyed information on future macroeconomic conditions by looking at the reaction of private sector expectations as measured in survey forecasts (Romer and Romer 2000, Campbell et al 2012, Andrade, Gaballo, Mengus and Mojon 2015. Several recent studies provide evidence that information about future states can be found even in intraday monetary policy surprises.…”
Section: Related Literaturementioning
confidence: 99%
“…Another closely related paper comes from Andrade et al. (). These authors study forward guidance under heterogeneous beliefs of market participants.…”
mentioning
confidence: 97%
“…Krugman (1998) is a seminal paper in this literature. More recent papers in this literature areLevin et al (2010),Laséen and Svensson (2011), Werning (2011), Campbell et al (2012,Milani and Treadwell (2012),Carlstrom, Fuerst, and Paustian (2015),Del Negro, Giannoni, and Patterson (2015),Bundick and Smith (2016),Campbell et al (2016), and McKay,Nakamura, and Steinsson (2016).2Ellingsen and Söderström (2001),Frankel and Katrik (2015),Tang (2015),Gaballo (2016),Melosi (2017),Andrade et al (2018),Jarociński and Karadi (2018), and Jia (2018) also provide models where central bank policy reveals private information or coordinates dispersed information.…”
mentioning
confidence: 99%